2008
DOI: 10.1088/1126-6708/2008/04/083
|View full text |Cite
|
Sign up to set email alerts
|

Selfdual strings and loop space Nahm equations

Abstract: We give two independent arguments why the classical membrane fields should be take values in a loop algebra. The first argument comes from how we may construct selfdual strings in the M5 brane from a loop space version of the Nahm equations. The second argument is that there appears to be no infinite set of finite-dimensional Lie algebras (such as su(N ) for any N ) that satisfies the algebraic structure of the membrane theory.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
276
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 244 publications
(281 citation statements)
references
References 23 publications
5
276
0
Order By: Relevance
“…Subsequent work [4][5][6] revealed that such CSm theories, which can be generalized to SU(N )×SU(M ) [7,8], are equivalent to theories constructed using three-algebras whose structure constants enjoy lesser symmetry compared with that of the BLG theory.…”
Section: Jhep11(2013)050mentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent work [4][5][6] revealed that such CSm theories, which can be generalized to SU(N )×SU(M ) [7,8], are equivalent to theories constructed using three-algebras whose structure constants enjoy lesser symmetry compared with that of the BLG theory.…”
Section: Jhep11(2013)050mentioning
confidence: 99%
“…This is the SO(4) = SU(2) × SU(2) threealgebra that was constructed by BLG [4][5][6]. More generally, we will refer to the theory with g = −g and totally antisymmetric f abcd as BLG-type theories.…”
Section: Jhep11(2013)050mentioning
confidence: 99%
See 2 more Smart Citations
“…The first one is based on the Lie superalgebra F (4). The embedding tensor reads (where a, b, .. refer to the spinor representation 8 of SO (7) and α, β, .. denote an SL(2) doublet)…”
Section: Solving the Constraintsmentioning
confidence: 99%